Systeme D#x2019;information Comptable Et Performance Globale Des Entreprises Industrielles Au Cameroun (Global Journal of Management and Business Research, 2020)
This paperaims to identify the link between the quality of the Accounting Information System and Performance within industrial organizations. Building on the model of Ives, Hamilton and Davis (1980) and Raymond (1984), this study focusses on five Cameroonian industrial companies. The results from the analys is of the collected datas en able us to identify some performance mechanisms and to propose a cameroonian model of global performance based on the Accounting Information System.
Keywords: accounting information system; industrial organization; global performance